2014
DOI: 10.3390/ijerph110808383
|View full text |Cite
|
Sign up to set email alerts
|

Practical Barriers and Ethical Challenges in Genetic Data Sharing

Abstract: The underlying ethos of dbGaP is that access to these data by secondary data analysts facilitates advancement of science. NIH has required that genome-wide association study data be deposited in the Database of Genotypes and Phenotypes (dbGaP) since 2003. In 2013, a proposed updated policy extended this requirement to next-generation sequencing data. However, recent literature and anecdotal reports suggest lingering logistical and ethical concerns about subject identifiability, informed consent, publication em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 30 publications
(37 reference statements)
0
15
0
Order By: Relevance
“…This is a significant concern of some data producers because they see access review either as a mechanism to maintain control of downstream use of data or as an opportunity to collaborate with data users. 32…”
Section: Discussionmentioning
confidence: 99%
“…This is a significant concern of some data producers because they see access review either as a mechanism to maintain control of downstream use of data or as an opportunity to collaborate with data users. 32…”
Section: Discussionmentioning
confidence: 99%
“…60 It is similar to PERSPECTIVE's association with BCAC. Although consortia can provide tremendous support for efficient data sharing, they have some limits.…”
Section: Conclusion: Facilitating Future Data Sharingmentioning
confidence: 94%
“…29 In accessing the dbGaP, there is variation in whether IRB approval is required. 30 However, in gaining IRB approval for data submission to dbGaP, some researchers reported that IRBs restricted release of data to dbGaP by requiring the reconsent of research participants. 31 The National Cancer Institute (NCI) has issued best practices for NCI-supported "biospecimen resources," which cover operational, technical, ethical, legal, and policy aspects of biospecimens.…”
Section: Specimen and Data Accessmentioning
confidence: 99%